Urinary Dysfunction in Progressive Supranuclear Palsy Compared with Other Parkinsonian Disorders. - Tatsuya Yamamoto; Fuyuki Tateno; Ryuji Sakakibara; Shogo Furukawa; Masato Asahina; Tomoyuki Uchiyama; Shigeki Hirano; Yoshitaka Yamanaka; Miki Fuse; Yasuko Koga; Mitsuru Yanagisawa; Satoshi Kuwabara (PLoS ONE, 2016)
BACKGROUND:Autonomic urinary dysfunction affects patients with progressive supranuclear palsy (PSP); however, the severity and prevalence of urinary dysfunctions in these patients compared with those observed in patients with Parkinson's disease (PD) and multiple system atrophy (MSA) are unknown. OBJECTIVE:We compared urinary dysfunction characteristics in patients with PSP, PD, and MSA. PATIENTS AND METHODS:Forty-seven patients who satisfied the probable or possible criteria of the National Institute for Neurological Diseases and Stroke and Society for PSP were assessed using the urinary symptoms questionnaire and the urodynamic study at Chiba and Toho Universities (n = 26 and 21, respectively). The results were compared with those of patients with PD and MSA (n = 218 and 193, respectively). RESULTS:The mean disease duration of PSP and the mean age were 2.97 ± 0.26 and 71.4 ± 0.88 years, respectively. The mini-mental state examination and frontal assessment battery scores were 22.6 ± 0.70 and 10.7 ± 0.49, respectively. Urinary storage and voiding symptoms were observed in 57% and 56% of patients with PSP, respectively. Detrusor overactivity in the urodynamic study was detected in 81% of patients with PSP, which was slightly more than that found in patients with PD (69%) and MSA (67%); however, this was not statistically significant. Postvoid residual volume in patients with PSP was significantly more than that in patients with PD (P < 0.01), but was equivalent to that in patients with MSA. CONCLUSIONS:The present study demonstrated that patients with PSP experienced various urinary dysfunctions. Urinary storage dysfunction in patients with PSP was not different from that in patients with PD or MSA, whereas urinary voiding dysfunction in patients with PSP was milder than that in patients with MSA and more severe than that in patients with PD. These features should be taken into account for the differentiation of PSP from PD and MSA.